Theft in the Family Context: An Analysis of Article 367 of the Criminal Code and its Application in Indonesia - Hanafi; Khalid, Afif; Wardiansyah, Gusti; Hidayatullah (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This study aims to explore the regulation and implementation of family criminal law regarding theft cases within a family context from the perspectives of Indonesia Criminal Codes (KUHP) and the theory of jarimah of the Islamic criminal law. By employing a descriptive qualitative method with a literature review approach, the research analyzes legal sources and relevant literature. The findings reveal that theft is generally regarded as a common crime. However, in specific contexts, such as theft occurring within a family setting, special provisions outlined in Article 367 of the KUHP. This article classifies family theft as a complaint offense (klacht delict), meaning it can only be prosecuted if there is a complaint from the aggrieved party. The study underscores the importance of thoroughly understanding the characteristics of family theft and its implications for the criminal justice system. It also highlights the need for further evaluation of the effectiveness and application of this law in the Indonesian family context, incorporating insights from the theory of jarimah in Islamic criminal law.